The Relationship Between Brushing Habits And Oral Hygiene Status (Ohi-S) In Students Of Sd Negeri Kandang Cut, Darul Imarah District, Aceh Regency - Andriani, Andriani; Nur, Arnela; Keumala , Cut Ratna (Jurusan Kesehatan Gigi Poltekkes Kemenkes Aceh, 2023)
Regular teeth cleaning is a treatment for dental and oral diseases that can be done alone. How to brush your teeth properly and appropriately will help improve dental and oral hygiene so as to prevent the occurrence of periodontal disease and caries. The purpose of the study was to determine the relationship between brushing teeth and oral hygiene in grade IV and V students of SDN Kandang Cut, Darul Imarah District, Aceh Besar Regency in 2022. The research was conducted using analytical methods from 18 to 21 April 2022. The study population numbered 40 people. The number of samples taken in this study used a saturated sample of 40 students. Data collection by checking dental and oral hygiene using OHIS index and observation of how to brush teeth using cheklist. The analysis used univariate and bivariate analysis using a statistical chi-square test α < 0.05 The results of the study of students who brushed their teeth correctly had the most dental and oral hygiene status on good criteria amounted to 7 respondents (70%) while students who brushed their teeth incorrectly had the most dental and oral hygiene status on bad criteria amounted to 15 respondents (50%). The results of the chi-square statistical test obtained P Value <from α namely P = 0.001 < 0.05, then there is a relationship between how to brush your teeth with dental and oral hygiene. It was concluded that there is a relationship between brushing teeth and oral hygiene in grade IV and V students of SD Negeri Kandang Cut, Darul Imarah District, Aceh Besar Regency in 2022. It is recommended for students to improve and apply how to brush their teeth properly and correctly, especially on the inside that is often overlooked.